Amidoximated polyacrylonitrile fiber as well as preparation method and application thereof

By irradiating, alkali treatment and geminoximetization of polyacrylonitrile fibers, efficient geminoximetization of polyacrylonitrile fibers were prepared, which solved the problems of high cost of adsorbents and slow adsorption speed in the existing seawater uranium extraction technology, and achieved rapid and efficient adsorption of uranium in seawater.

CN119900169APending Publication Date: 2025-04-29INST OF MODERN PHYSICS CHINESE ACADEMY OF SCI
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411894470.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

In the existing seawater uranium extraction technology, the adsorbent preparation cost is high and the adsorption rate of uranium in seawater is slow. Long-term soaking will lead to corrosion of adsorbent materials and microbial contamination, reducing the performance of uranium extraction.

Method used

By irradiating the polyacrylonitrile fibers, alkali treatment, geminoximetization reaction and re-base treatment, geminoximetization polyacrylonitrile fibers are prepared to increase their adsorption rate and adsorption amount to uranium.

Benefits of technology

It significantly increases the adsorption rate and adsorption amount of uranium by amidoximetyl polyacrylonitrile fibers, and is suitable for rapid adsorption in low-content uranium environments, avoids corrosion of seawater on adsorbent materials and reduces preparation costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119900169A_ABST
    Figure CN119900169A_ABST
Patent Text Reader

Abstract

The invention provides an amidoximation polyacrylonitrile fiber as well as a preparation method and application thereof. The method comprises the following steps: (1) carrying out irradiation treatment on a polyacrylonitrile fiber; (2) soaking the polyacrylonitrile fibers subjected to irradiation treatment with an alkali solution to obtain alkali-treated polyacrylonitrile fibers; (3) carrying out amidoximation reaction on the alkali-treated polyacrylonitrile fibers to obtain amidoximated polyacrylonitrile fibers; and (4) soaking the amidoximated polyacrylonitrile fiber in an alkali solution, washing and drying. According to the method, irradiation treatment and two times of alkali treatment are combined, the adsorption rate and adsorption capacity of the amidoximation polyacrylonitrile fiber to uranium are remarkably improved, rapid adsorption of uranium in seawater can be achieved, corrosion of seawater to an adsorption material is avoided, the method is easy to operate, the adopted polyacrylonitrile fiber is low in cost, and the method is suitable for industrial production. The method is suitable for large-scale seawater uranium extraction material preparation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer materials, and in particular to amidoximated polyacrylonitrile fiber and a preparation method and application thereof. Background Art

[0002] As the main fuel of nuclear power, uranium is an important guarantee for the development of nuclear power. With the rapid development of my country's nuclear power industry, the demand for raw uranium is increasing day by day. In the future economic and national defense construction, the guarantee level of raw uranium will be related to the sustained and stable development of the national economy.

[0003] In addition to uranium mines on land, seawater also contains 4.5 billion tons of uranium, which is 1,000 times the proven uranium reserves on land. If uranium in seawater is extracted and utilized, it can meet the needs of human nuclear energy development for thousands of years and realize the "unlimited endurance" of the nuclear energy industry. The research and development of uranium extraction technology from seawater in various countries around the world focuses on direct adsorption extraction with adsorption materials as the core. Adsorbents containing amidoxime groups have attracted widespread attention in the field of uranium extraction from seawater due to their good selectivity for uranium adsorption. At present, researchers have prepared adsorbents containing amidoxime groups through various methods, but these adsorbents generally have high preparation costs and are not suitable for engineering applications of uranium extraction from seawater. At the same time, seawater has a certain degree of corrosiveness. The current adsorption rate of uranium in seawater by adsorption materials is relatively slow. In order to increase the adsorption amount of uranium, the adsorption materials must be immersed in seawater for a long time. However, long-term immersion in seawater will cause serious corrosion and microbial contamination to the adsorption materials, which will further reduce the uranium extraction performance and reusability of the adsorption materials. Summary of the invention

[0004] The present invention aims to solve one of the technical problems in the prior art at least to a certain extent. To this end, one object of the present invention is to provide an amidoximated polyacrylonitrile fiber and a preparation method and application thereof.

[0005] In a first aspect of the present invention, the present invention provides a method for preparing amidoximated polyacrylonitrile fiber, the method comprising: (1) Irradiating polyacrylonitrile fiber; (2) soaking the irradiated polyacrylonitrile fiber in an alkali solution to obtain alkali-treated polyacrylonitrile fiber; (3) subjecting the alkali-treated polyacrylonitrile fiber to an amidoximation reaction to obtain amidoximated polyacrylonitrile fiber; (4) The amidoximated polyacrylonitrile fiber is soaked in an alkaline solution, washed and dried.

[0006] According to the preparation method of the amidoximated polyacrylonitrile fiber provided by the present invention, the polyacrylonitrile fiber is firstly subjected to irradiation treatment to introduce defects into the polyacrylonitrile fiber by irradiation treatment; then the irradiated polyacrylonitrile fiber is soaked in an alkaline solution, and the defects can be exposed as much as possible by the alkali treatment, which is more conducive to the subsequent amidoximation reaction of the nitrile group; then the alkali-treated polyacrylonitrile fiber is subjected to an amidoximation reaction to obtain amidoximated polyacrylonitrile fiber; finally, the obtained amidoximated polyacrylonitrile fiber is treated with alkali again, and the alkali treatment can effectively improve the hydrophilicity of the amidoximated polyacrylonitrile fiber, improve the utilization rate of the amidoximation group, and thus improve the adsorption rate and adsorption amount of uranium by the adsorption material. Therefore, the present invention significantly improves the adsorption rate and adsorption amount of uranium by the amidoxime-treated polyacrylonitrile fiber by sequentially irradiating, alkali treating, amidoximating and then alkali treating the polyacrylonitrile fiber, and can effectively enrich and quickly adsorb uranium in an environment with low uranium content, thereby realizing rapid adsorption of uranium in seawater, thereby avoiding corrosion of the adsorption material by seawater, and the method is simple to operate, and the polyacrylonitrile fiber used is low in cost, and is suitable for the preparation of large-scale seawater uranium extraction materials.

[0007] According to the preparation method of amidoximated polyacrylonitrile fiber provided by the present invention, in step (1), the irradiation dose of the irradiation treatment is 20kGy-1000kGy, preferably 100kGy-500kGy. For example, the irradiation dose is 20kGy, 50kGy, 100kGy, 200kGy, 300kGy, 400kGy, 500kGy, 600kGy, 800kGy, 1000kGy, etc., or the range between any two of the above values. By controlling the irradiation dose of the irradiation treatment of the polyacrylonitrile fiber within the above range, more defects can be introduced into the polyacrylonitrile fiber as much as possible, thereby improving the adsorption performance of the adsorbent material for uranium.

[0008] Furthermore, the radiation source used in the radiation treatment includes a cobalt source or an electron beam.

[0009] According to the method for preparing amidoxime-modified polyacrylonitrile fiber provided by the present invention, in step (2), the concentration of the alkaline solution is 0.1mol / L-1mol / L, preferably 0.2mol / L-0.5mol / L. For example, the concentration of the alkaline solution is 0.1mol / L, 0.2mol / L, 0.3mol / L, 0.4mol / L, 0.5mol / L, 0.6mol / L, 0.7mol / L, 0.8mol / L, 0.9mol / L, 1mol / L, etc., or the range between any two values ​​of the above. By controlling the concentration of the alkaline solution within the above range, as many defects as possible can be exposed, which is beneficial to increase the amidoxime content in the adsorbent material, thereby improving the adsorption capacity of the adsorbent material for uranium.

[0010] Furthermore, the alkaline solution includes but is not limited to sodium hydroxide solution or potassium hydroxide solution.

[0011] According to the preparation method of amidoxime polyacrylonitrile fiber provided by the present invention, in step (2), the soaking time of the alkaline solution is 4h-10h, preferably 5h-7h. For example, the soaking time is 4h, 5h, 6h, 7h, 8h, 9h, 10h, etc., or the range between any two of the above values. By controlling the soaking time of the alkaline solution within the above range, more defects can be exposed as much as possible, which is beneficial to increase the amidoxime content in the adsorbent material, thereby improving the adsorption capacity of the adsorbent material for uranium.

[0012] Preferably, the irradiated polyacrylonitrile fiber is soaked in an alkaline solution, the concentration of the alkaline solution is 0.2 mol / L-0.5 mol / L, and the soaking time of the alkaline solution is 5 h-7 h.

[0013] According to the method for preparing amidoximated polyacrylonitrile fiber provided by the present invention, in step (2), ultrasonic cleaning is performed after the alkali solution soaking is completed, and the ultrasonic cleaning time is 20min-60min. A small amount of alkali will remain in the fiber after alkali soaking, so the polyacrylonitrile fiber obtained by alkali soaking treatment is placed in an ultrasonic cleaner (put in water) for ultrasonic treatment, washed to neutrality, thereby removing the residual alkali. It should be noted that the present invention does not specifically limit the power of ultrasound, and those skilled in the art can make a choice according to actual conditions.

[0014] According to the method for preparing amidoximated polyacrylonitrile fiber provided by the present invention, in step (3), the amidoximation reaction comprises: the alkali-treated polyacrylonitrile fiber undergoes an amidoximation reaction with hydroxylamine hydrochloride in an aqueous solution.

[0015] Preferably, the mass ratio of the alkali-treated polyacrylonitrile fiber to the hydroxylamine hydrochloride is 1:(0.8-1.2), preferably 1: 1. For example, the mass ratio of the alkali-treated polyacrylonitrile fiber to the hydroxylamine hydrochloride is 1:0.8, 1:0.9, 1:1, 1:1.1, 1:1.2, etc., or a range between any two of the above values.

[0016] Preferably, the reaction temperature during the amidoximation reaction is 65-75°C, preferably 68°C-72°C, and the reaction time is 5h-15h, preferably 10h-12h.

[0017] Preferably, the pH of the aqueous solution is 6-11.

[0018] According to the preparation method of amidoximated polyacrylonitrile fiber provided by the present invention, in step (4), the concentration of the alkaline solution is 0.1-1 mol / L, preferably 0.2-0.6 mol / L. For example, the concentration of the alkaline solution is 0.1 mol / L, 0.2 mol / L, 0.3 mol / L, 0.4 mol / L, 0.5 mol / L, 0.6 mol / L, 0.7 mol / L, 0.8 mol / L, 0.9 mol / L, 1 mol / L, etc., or the range between any two of the above values. By controlling the concentration of the alkaline solution within the above range, the hydrophilicity of the amidoximated polyacrylonitrile fiber can be effectively improved, thereby increasing the adsorption rate and adsorption amount of uranium by the adsorbent material.

[0019] Furthermore, in step (4), the alkaline solution includes but is not limited to sodium hydroxide solution or potassium hydroxide solution.

[0020] According to the preparation method of amidoximated polyacrylonitrile fiber provided by the present invention, in step (4), the soaking time of the alkaline solution is 3h-10h, preferably 5h-6h. For example, the soaking time is 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, etc., or the range between any two of the above values. By controlling the soaking time of the alkaline solution within the above range, the hydrophilicity of the amidoximated polyacrylonitrile fiber can be effectively improved, thereby increasing the adsorption rate and adsorption amount of uranium by the adsorbent material.

[0021] Preferably, the amidoximated polyacrylonitrile fiber is soaked in an alkali solution, washed, and dried, the concentration of the alkali solution is 0.2-0.6 mol / L, and the soaking time of the alkali solution is 5h-6h.

[0022] According to the method for preparing amidoximated polyacrylonitrile fiber provided by the present invention, in step (4), the drying temperature is 60-100° C., preferably 60-80° C. It should be noted that the drying method includes but is not limited to vacuum freeze drying, drying or vacuum drying. For drying or vacuum drying, the above-mentioned drying temperature and time can be selected. For the specific drying method, those skilled in the art can select it according to actual conditions.

[0023] In a second aspect of the present invention, the present invention provides an amidoximated polyacrylonitrile fiber, which is prepared by the above method. Thus, the amidoximated polyacrylonitrile fiber has a large adsorption rate and adsorption amount for uranium, can achieve rapid adsorption of uranium in seawater, avoid corrosion of the adsorption material by seawater, and extend the service life of the adsorption material.

[0024] In the third aspect of the present invention, the present invention proposes the use of the amidoximated polyacrylonitrile fiber in adsorbing uranium in seawater.

[0025] Seawater is rich in uranium resources. The amidoximated polyacrylonitrile fiber of the present invention can effectively enrich and adsorb uranium in an environment with a low uranium concentration, and the adsorption rate is fast. For example, it is suitable for seawater with a uranium concentration of 20 ng / mL, 15 ng / mL, 10 ng / mL, etc., and the adsorption speed is fast. Specifically, most of the uranium in seawater can be adsorbed within 1-3 days, which significantly improves the application value of uranium in seawater. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0027] Figure 1 This is a physical picture of the amidoximated polyacrylonitrile fiber finally obtained in Example 1 of the present invention and Comparative Example 1; Figure 2 It is the infrared spectrum of the irradiated polyacrylonitrile fiber and the amidoximated polyacrylonitrile fiber of Example 1 of the present invention and the infrared spectrum of the non-irradiated polyacrylonitrile fiber and the amidoximated polyacrylonitrile fiber of Comparative Example 1. DETAILED DESCRIPTION

[0028] Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. The present invention is described below with reference to specific embodiments. It should be noted that these embodiments are merely illustrative and do not limit the present invention in any way.

[0029] Example 1 The preparation process of the amidoximated polyacrylonitrile fiber of this embodiment is as follows: (1) Take 500g of polyacrylonitrile fiber (produced by Shenying Carbon Fiber Co., Ltd.) 60 Irradiation on Co source.

[0030] (2) Accurately weigh 2.0 g of polyacrylonitrile fiber with an irradiation dose of 100 kGy, soak it in a prepared 0.2 mol / L sodium hydroxide solution for 6 h, and then place it in an ultrasonic cleaner and ultrasonicate it at full power for 30 min.

[0031] (3) Accurately weigh 2.0 g of hydroxylamine hydrochloride, 2.6 g of anhydrous sodium carbonate and 0.6 g of sodium hydroxide, dissolve them in 100 mL of deionized water, and continue to adjust the pH to 10.0 with sodium hydroxide. Pour the hydroxylamine hydrochloride solution with adjusted pH into a 250 mL three-necked flask.

[0032] (4) Add 2 g of the alkali-treated polyacrylonitrile fiber obtained in step (2) into the three-necked flask containing the hydroxylamine hydrochloride solution in step (3), ensuring that all fiber strands are fully immersed, and heat to 70° C. to continue the amidoximation reaction for 12 h. At the same time, in order to avoid fiber entanglement caused by stirring, the entire amidoximation process is carried out in a static state.

[0033] (5) When the system of step (4) is cooled to room temperature, the obtained amidoximated polyacrylonitrile fiber is washed with deionized water until it is neutral, and then immersed in a 0.2 mol / L sodium hydroxide solution for 6 h.

[0034] (6) After the soaking is completed, the amidoxime-treated polyacrylonitrile fiber is washed to neutrality, and freeze-dried or vacuum-dried to obtain amidoxime-treated polyacrylonitrile fiber.

[0035] Example 2 The difference between the method for preparing amidoximated polyacrylonitrile fiber in this embodiment and that in embodiment 1 is as follows: (2) Accurately weigh 2.0 g of polyacrylonitrile fiber with an irradiation dose of 200 kGy, soak it in a prepared 0.2 mol / L sodium hydroxide solution for 6 h, and then place it in an ultrasonic cleaner and ultrasonicate it at full power for 30 min.

[0036] Comparative Example 1 The preparation process of the amidoximated polyacrylonitrile fiber of this comparative example is as follows: (1) Accurately weigh 2.0 g of polyacrylonitrile fiber and soak it in a 0.2 mol / L sodium hydroxide solution for 6 h. After soaking, place it in an ultrasonic cleaner and ultrasonicate it at full power for 30 min.

[0037] (2) Accurately weigh 2.0 g of hydroxylamine hydrochloride, 2.6 g of anhydrous sodium carbonate and 0.6 g of sodium hydroxide, dissolve them in 100 mL of deionized water, and continue to adjust the pH to 10.0 with sodium hydroxide. Pour the hydroxylamine hydrochloride solution with adjusted pH into a 250 mL three-necked flask.

[0038] (3) Add the alkali-treated polyacrylonitrile fiber obtained in step (1) into the three-necked flask containing the hydroxylamine hydrochloride solution in step (2) to ensure that all fiber filaments are fully immersed, and heat to 70° C. to continue the amidoximation reaction for 12 hours. At the same time, in order to avoid fiber entanglement caused by stirring, the entire amidoximation process is carried out in a static state.

[0039] (4) When the system of step (3) is cooled to room temperature, the obtained amidoximated polyacrylonitrile fiber is washed with deionized water until it is neutral, and then immersed in a 0.2 mol / L sodium hydroxide solution for 6 hours.

[0040] (5) After the soaking is completed, the amidoxime-treated polyacrylonitrile fiber is washed to neutrality, and freeze-dried or vacuum-dried to obtain amidoxime-treated polyacrylonitrile fiber.

[0041] Comparative Example 2 The preparation process of the amidoximated polyacrylonitrile fiber of this comparative example is as follows: (1) Take a certain amount of polyacrylonitrile fiber and 60 Co source, and accurately weigh 2.0 g of polyacrylonitrile fiber with an irradiation dose of 100 kGy.

[0042] (2) Accurately weigh 2.0 g of hydroxylamine hydrochloride, 2.6 g of anhydrous sodium carbonate and 0.6 g of sodium hydroxide, dissolve them in 100 mL of deionized water, and continue to adjust the pH to 10.0 with sodium hydroxide. Pour the hydroxylamine hydrochloride solution with adjusted pH into a 250 mL three-necked flask.

[0043] (3) Add the irradiated polyacrylonitrile fiber of step (1) into the three-necked flask containing the hydroxylamine hydrochloride solution of step (2), ensure that all fiber strands are fully immersed, raise the temperature to 70°C and continue the amidoximation reaction for 12 hours. At the same time, in order to avoid fiber entanglement caused by stirring, the entire amidoximation process is carried out in a static state.

[0044] (4) After the oximation reaction is completed, the system is cooled to room temperature, and the amidoximated polyacrylonitrile fiber is washed to neutrality and freeze-dried or vacuum-dried.

[0045] The properties of the polyacrylonitrile fibers of the embodiments and comparative examples were verified as follows: (1) The actual pictures of the amidoximated polyacrylonitrile fibers finally obtained in Example 1 and Comparative Example 1 are as follows: Figure 1 As shown, from Figure 1 It can be seen that after irradiation treatment, the color of the fiber is obviously darker and more uniform than that of the non-irradiated fiber, indicating that after irradiation treatment, the degree of amidoximation of the polyacrylonitrile fiber is higher.

[0046] (2) The infrared spectra of the irradiated polyacrylonitrile fiber and the amidoximated polyacrylonitrile fiber of Example 1 and the infrared spectra of the non-irradiated polyacrylonitrile fiber and the amidoximated polyacrylonitrile fiber of Comparative Example 1 are shown in FIG. Figure 2 As shown, from Figure 2 It can be seen that the degree of amidoximation of polyacrylonitrile fiber after irradiation treatment is higher.

[0047] (3) Experiment on the adsorption of uranium in simulated seawater Simulated seawater was prepared with sea salt and its pH was adjusted to 8.0 and the uranium concentration was 20 ng / mL. 5 mg of amidoxime-modified polyacrylonitrile fiber was accurately weighed and added to a conical flask containing 75 mL of simulated seawater. The conical flask was placed on a constant temperature shaking table at 200 rpm at room temperature for 48 hours. The uranium concentration in the simulated seawater before and after adsorption was determined using a trace uranium analyzer.

[0048] The calculation formula for the adsorption of uranium is: e =(C0-C e )V / m Where: C0 and C e are the uranium concentrations in the simulated seawater at the initial stage and at adsorption equilibrium (ng / mL), V is the volume of the simulated seawater used (mL), and m is the mass of the amidoximated polyacrylonitrile fiber (mg).

[0049] Uranium adsorption rate per day V U (ng / mg / d) is calculated as: U =q e / d Where d is the number of days the adsorbent material is in contact with simulated seawater.

[0050] The results of the uranium adsorption experiment of the amidoximated polyacrylonitrile fibers of the examples and comparative examples in simulated seawater are shown in Table 1.

[0051] Table 1

[0052] It can be seen from Table 1 that under the same amidoximation treatment conditions, both irradiation and alkali treatment can improve the amidoximation degree of polyacrylonitrile fiber. In particular, the present invention first performs irradiation and then performs a two-step alkali treatment, which can significantly improve the adsorption effect of amidoximated polyacrylonitrile fiber on uranium.

[0053] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing amidoximated polyacrylonitrile fiber, characterized in that: include: (1) Irradiating polyacrylonitrile fiber; (2) soaking the irradiated polyacrylonitrile fiber in an alkali solution to obtain alkali-treated polyacrylonitrile fiber; (3) subjecting the alkali-treated polyacrylonitrile fiber to an amidoximation reaction to obtain amidoximated polyacrylonitrile fiber; (4) The amidoximated polyacrylonitrile fiber is soaked in an alkaline solution, washed and dried.

2. The method according to claim 1, characterized in that: In step (1), the irradiation dose of the irradiation treatment is 20 kGy-1000 kGy; And / or, the radiation source used in the radiation treatment includes a cobalt source or an electron beam.

3. The method according to claim 2, characterized in that: The irradiation dose of the irradiation treatment is 100 kGy-500 kGy.

4. The method according to any one of claims 1 to 3, characterized in that: In step (2), the concentration of the alkaline solution is 0.1 mol / L-1 mol / L; And / or, the immersion time of the alkaline solution is 4h-10h.

5. The method according to any one of claims 1 to 3, characterized in that: In step (2), the alkaline solution includes sodium hydroxide solution or potassium hydroxide solution.

6. The method according to any one of claims 1 to 3, characterized in that: In step (3), the amidoximation reaction comprises: mixing the alkali-treated polyacrylonitrile fiber and hydroxylamine hydrochloride in an aqueous solution to undergo an amidoximation reaction.

7. The method according to claim 6, characterized in that: The mass ratio of the alkali-treated polyacrylonitrile fiber to the hydroxylamine hydrochloride is 1:(0.8-1.2); And / or, the reaction temperature during the amidoximation reaction is 65-75° C., and the reaction time is 5 h-15 h; And / or, the pH of the aqueous solution is 6-11.

8. The method according to any one of claims 1 to 3, characterized in that: In step (4), the concentration of the alkaline solution is 0.1 mol / L-1 mol / L; And / or, the alkaline solution includes sodium hydroxide solution or potassium hydroxide solution; And / or, the immersion time of the alkaline solution is 3h-10h.

9. An amidoximated polyacrylonitrile fiber, characterized in that: The method is prepared by any one of claims 1 to 8.

10. Use of the amidoximated polyacrylonitrile fiber according to claim 9 in adsorbing uranium in seawater.

Citation Information

Cited By

  • Rock wool insulation board adhesive mortar and preparation method thereof

    CN122355627A